Da autonomia do indivíduo à responsabilidade solidária - Tavares, Sinivaldo Silva (Revista eclesiástica brasileira, 2007)
Having as background the phenomenon of the “exculturation of Christianity” the article attempts to show that it has become necessary to reclaim the human being’s dignity in a perspective other than the mere economic and secular one. It describes the decisive contribution of the Jewish-Christian Revelation to the blossoming of a new consciousness of human dignity and focuses on the person of Jesus of Nazareth as the highest point of this historical process. Jesus, the Son of God, “made Himself weak among the weak and with the weak” and empathized with human vulnerability. Jesus revealed the creature’s supreme dignity and founded a new ethic, the ethic of responsibility and solidarity. This responsibility includes caring for all live beings and for the integrity of nature, God’s work.